2022
DOI: 10.1177/17562848221074183
|View full text |Cite
|
Sign up to set email alerts
|

Risk of bias in non-randomized observational studies assessing the relationship between proton-pump inhibitors and adverse kidney outcomes: a systematic review

Abstract: Background: Proton-pump inhibitors (PPIs) are widely prescribed as acid-suppression therapy. Some observational studies suggest that long-term use of PPIs is potentially associated with certain adverse kidney outcomes. We conducted a systematic literature review to assess potential bias in non-randomized studies reporting on putative associations between PPIs and adverse kidney outcomes (acute kidney injury, acute interstitial nephritis, chronic interstitial nephritis, acute tubular necrosis, chronic kidney di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
2
1
Order By: Relevance
“…Regarding the systematic reviews across countries from the United States, Brazil, Taiwan, Sweden, and Denmark, effect estimates for the association between PPI treatment (compared with non-PPI users or H2 blocker users) and CKD ranged from an adjusted HR of 1.12 (95% CI 1.08-1.17) to 7.34 (95% CI 3.94-13.71). 23 As compared with this study, Guedes et al 10 resulted the HR was 7.34 (95% CI: 3.94-13.71) (Supplementary Table 3A), indicating a higher risk of worse stages of CKD in omeprazole users than in non-users. This is relevant to our sub-group analysis (Table 4) that HR among omeprazole as compared to H2RAs was 3.783 (95% CI: 2.404-5.952).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Regarding the systematic reviews across countries from the United States, Brazil, Taiwan, Sweden, and Denmark, effect estimates for the association between PPI treatment (compared with non-PPI users or H2 blocker users) and CKD ranged from an adjusted HR of 1.12 (95% CI 1.08-1.17) to 7.34 (95% CI 3.94-13.71). 23 As compared with this study, Guedes et al 10 resulted the HR was 7.34 (95% CI: 3.94-13.71) (Supplementary Table 3A), indicating a higher risk of worse stages of CKD in omeprazole users than in non-users. This is relevant to our sub-group analysis (Table 4) that HR among omeprazole as compared to H2RAs was 3.783 (95% CI: 2.404-5.952).…”
Section: Discussioncontrasting
confidence: 50%
“…Regarding the systematic reviews across countries from the United States, Brazil, Taiwan, Sweden, and Denmark, effect estimates for the association between PPI treatment (compared with non-PPI users or H2 blocker users) and CKD ranged from an adjusted HR of 1.12 (95% CI 1.08–1.17) to 7.34 (95% CI 3.94–13.71). 23 …”
Section: Discussionmentioning
confidence: 99%
“…Fourth, although we demonstrated that the incidence rate of CIO was significantly lower in patients treated with LPZ compared to those treated without LPZ in the EHRs of Mie University Hospital, the number of patients with CIO (n = 29) was relatively low among the total number of patients (n = 260). Additional real-world evidence among general populations is required to confirm whether LPZ or other PPIs can protect against CIO (Rajan et al, 2022). Fifth, we were not able to analyze the effect of LPZ on the survival of patients treated with CDDP.…”
Section: Discussionmentioning
confidence: 97%